Solving the conundrum of Job: a probable biblical description of chronic renal failure with neurological symptoms - Resende, Luiz Antonio de Lima [UNESP]; Kirchner, Daniel Rocco [UNESP]; Resende, Lucilene Silva Ruiz e [UNESP] (Academia Brasileira de Neurologia (ABNEURO), 2009)
A doença descrita no livro bíblico de Jó é controversa, e tem interessado a teólogos, psiquiatras e dermatologistas, há tempos. Neste trabalho os autores apontam para evidências do diagnóstico de insuficiência renal crônica com alterações neurológicas.

The disease described in the Bible' Book of Job is controversial and had been of interest of theologists, psychiatrists, and dermatologists for many years. We describe several signs and symptoms compatible with chronic renal failure with neurological alterations.
Resolvendo o enigma de Jó: uma provável descrição bíblica de insuficiência renal crônica com sintomas neurológicos
Keywords: bíblia; Jó; insuficiência renal crônica; bible; Job; chronic renal failure